2023
DOI: 10.1055/s-0042-1758448
|View full text |Cite
|
Sign up to set email alerts
|

Addenbrooke's cognitive examination III: diagnostic utility for detecting mild cognitive impairment and dementia in Parkinson's disease

Abstract: Background Cognitive deficit in Parkinson disease (PD) is an important cause of functional disability in these patients and early detection, with sensitive instruments, can contribute to longitudinal monitoring. Objective To investigate the diagnostic accuracy, sensitivity, and specificity of the Addenbrooke's Cognitive Examination-III in patients with PD, using the comprehensive neuropsychological battery as reference method. Methods Cross-sectional, observational, case-control study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The cognitive phenotype was heterogenous; the most common subtypes were amnestic and non-amnestic MCI (aMCI, naMCI) single domain (11.3% and 8.9%, respectively) [ 76 ]. More recent studies reported 69.3% PD-MCI, 16% PD with normal cognition (PD-NC) and 14.66% PDD [ 77 ] or 34% PD-MCI with 77.8% impaired in multiple cognitive domains [ 59 ].…”
Section: Epidemiology Of CI In Pdmentioning
confidence: 99%
“…The cognitive phenotype was heterogenous; the most common subtypes were amnestic and non-amnestic MCI (aMCI, naMCI) single domain (11.3% and 8.9%, respectively) [ 76 ]. More recent studies reported 69.3% PD-MCI, 16% PD with normal cognition (PD-NC) and 14.66% PDD [ 77 ] or 34% PD-MCI with 77.8% impaired in multiple cognitive domains [ 59 ].…”
Section: Epidemiology Of CI In Pdmentioning
confidence: 99%